Stock Liquidity and Auditor Choice - Qin, Juan (Journal of Applied Business and Economics, 2021)
This paper investigates whether firms’ stock liquidity is associated with their auditor choice. Papers that support stock liquidity reinforces institutional monitoring incentives are generally based on one of two arguments: intervening in management decisions by helping investors overcome free-rider problems, or disciplining management through the threat of exit. Since stock liquidity can enhance institutional monitoring, firms with higher stock liquidity may have incentives to hire higher quality auditors to satisfy the demand of institutional investors. As predict, I find that firms with liquid stocks are more likely to appoint higher quality auditors such as Big 4 and industry specialist.